I HATE MY JOB : PERSPECTIVE DARI JOB DESIGN & JOB SATISFACTION - Agung Wahyu Wicaksono; Darmawanta Sembiring; Arief Rusdiansyah; Parjan Parjan (BISMA: Jurnal Bisnis dan Manajemen, 2022)
This study discusses in detail the impact of job design on the job satisfaction of the treasurer of THRDA. Furthermore, the intervening variables that mediate the relationship between job design and job satisfaction will also be identified. These variables are remuneration, quality of work-life, promotion, teamwork, participative leadership, and organizational motivation. This research uses the quantitative method. The path analysis was operated using the Smart PLS application to analyze the data. The research instrument used is a questionnaire distributed to all treasurers of THRDA in Indonesia. Thirty-four treasurers out of 64 treasurers have filled out the questionnaire. The results showed that the job design of the treasurer did not affect the job satisfaction of the treasurer. Meanwhile, job design through the intervening variable has a significant indirect effect on the job satisfaction of the treasurer. Thus, the intervening variable has succeeded in fully mediating the relationship between job design and job satisfaction of the treasurer. Keywords: job design, job satisfaction, treasurer